A sad tale: has the small mussel Idas argenteus lost its symbionts?. (30th December 2014) - Rodrigues, Clara F.; Laming, Sven R.; Gaudron, Sylvie M.; Oliver, Graham; Le Bris, Nadine; Duperron, Sébastien
<x xml:space="preserve">Abstract</x> Idas argenteus (Bivalvia: Mytilidae) belongs to a genus of mussels that are often associated with sunken wood and vertebrate bones in the deep sea. By contrast to other species currently included within the genus Idas and other related genera, such as Bathymodiolus, I. argenteus was documented to lack chemosynthetic symbionts bacterial symbionts in its gills. In the present study, new specimens are assigned to I. argenteus based on shell and soft parts analysis. Molecular data confirm the absence or low abundance of symbionts. Phylogeny based on five genes indicates that the symbiont‐bearing I. washingtonius is the closest relative of I. argenteus. Symbiosis loss or extreme reduction is thus inferred to have occurred subsequent to the speciation event, 11–13 Mya. This is the first report of a loss of symbiosis within the clade of deep‐sea chemosynthetic mussels. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 398–405.